Local but not systemic administration of mesenchymal stromal cells ameliorates fibrogenesis in regenerating livers. Issue 9 (27th June 2019) - van der Helm, Danny; Barnhoorn, Marieke C.; de Jonge‐Muller, Eveline S. M.; Molendijk, Ilse; Hawinkels, Luuk J. A. C.; Coenraad, Minneke J.; van Hoek, Bart; Verspaget, Hein W.
Abstract: Chronic liver injury leads to the accumulation of myofibroblasts resulting in increased collagen deposition and hepatic fibrogenesis. Treatments specifically targeting fibrogenesis are not yet available. Mesenchymal stromal cells (MSCs) are fibroblast‐like stromal (stem) cells, which stimulate tissue regeneration and modulate immune responses. In the present study we assessed whether liver fibrosis and cirrhosis can be reversed by treatment with MSCs or fibroblasts concomitant to partial hepatectomy (pHx)‐induced liver regeneration. After carbon tetrachloride‐induced fibrosis and cirrhosis, mice underwent a pHx and received either systemically or locally MSCs in one of the two remaining fibrotic/cirrhotic liver lobes. Eight days after treatment, liver fibrogenesis was evaluated by Sirius‐red staining for collagen deposition. A significant reduction of collagen content in the locally treated lobes of the regenerated fibrotic and cirrhotic livers was observed in mice that received high dose MSCs. In the non‐MSC‐treated counterpart liver lobes no changes in collagen deposition were observed. Local fibroblast administration or intravenous administration of MSCs did not ameliorate fibrosis. To conclude, local administration of MSCs after pHx, in contrast to fibroblasts, results in a dose‐dependent on‐site reduction of collagen deposition in mouse models for liver fibrosis and cirrhosis.